REPRESENTATION OF MAKASSAR TRIBAL IDENTITY IN THE TODDOPULI PERFORMANCE IN THE STATE OF SIAM: A SEMIOTICS STUDY OF JOHN FISKE - Saputra, Andi Taslim; Budiarti, Nuramalia; Batara, Mohammad Arga; Bastian, Egis (Universitas Negeri Makassar, 2023)
The Toddopuli show in Negeri Siam tells the story of the struggle of the Makassarese tribe, who were forced to leave their home country for a new country. This show shows the dominant culture and identity of Makassar. This performance shows culture and identity through dialogue accompanied by aesthetic movements, the lyrics sung by the players, and the movements and songs of the players' behavior. It was later identified as a dance drama. This research is classified as qualitative research conducted in depth using descriptive analysis. To explain the representation of Makassar culture and identity, this is analyzed using John Fiske's semiotic surgical tools. As a result, the representation of Makassar culture and identity in this performance is implemented through dialogue, events, actions, poetry, and props. This theatrical performance reveals that Makassar's culture and identity place dialogue that has the character of struggle, and the values of struggle are discussed in the performance text. Daeng Mangalle and the Makassar warriors, who apply cultural characterization and ethnic identity to the Makassarese, characterize the language of performance texts, which are effective in constructing the culture and identity of the Makassar people.Keywords: Theater, Representation, Culture, Identity, Makassar